Raising awareness on global environmental challenges by bringing polar research closer to the society - Goździk, Agata (Polish Polar Research, 2024)
The effects of climate change are much more rapid and visible in the Arctic than in the rest of the globe. The Arctic is extremely attractive scientifically and cognitively. Therefore, polar regions may serve as some of the most captivating natural settings capable of engage society in discussions on environmental changes. The primary objective of this paper is to present selected initiatives implemented by the Institute of Geophysics, Polish Academy of Sciences that aimed to connect polar research with schools and society, and show evidence on their effectiveness, with special focus on pupils from primary and secondary schools. In this paper, an overview of the educational and science communication initiatives undertaken by the Institute of Geophysics PAS for schools and whole society is presented, with the focus on polar research. Next, some results of the evaluation studies for those projects, that conducted detailed impact assessment, are discussed. Based on the evaluation studies and on general not-structured feedback received from diverse audiences of Institute’s activities, positive impact of bringing polar research closer to the society was observed. Using the Arctic and polar research as a vehicle to inspire interest in science and to raise societal awareness of the environmental challenges in various groups of non-specialists may be a very effective mean of science communication.